Isolated metastasis of uterine leiomyosarcoma to the pancreas: Report of a case and review of the literature - Ozturk, Safak (Elsevier, 2014)
INTRODUCTION: Metastatic tumors of the pancreas are uncommon and rarely detectable clinically. Metastases to the pancreas are rare. We present a patient with pancreatic metastases from a leiomyosarcoma of the uterus and review the literature about the clinical features of pancreatic metastasis and its surgical management. PRESENTATION OF CASE: A 40-year-old woman, who underwent hysterectomy, left oophorectomy, omentectomy and lymp node dissection for leiomyosarcoma of the uterus. At the follow up, the patient complained of non-specific abdominal discomfort. Preoperative diagnosis were pancreatic pseudocyst, cystadenoma or cystadenocarcinoma. At laparotomy, a cystic mass was found in the tail of the pancreas which was invased to the transverse colon mesenterium and the spleen. Distal pancreatectomy with splenectomy and transverse colon resection was performed. Histologically, the tumor was evaluated as poorly differentiated leiomyosarcoma. DISCUSSION: Metastatic lesions of the pancreas are uncommon and less than 2% of all pancreatic malignancies. However a few cases of leiomyosarcoma with metastases to the pancreas have been reported in the literature. Before deciding that the lesion in the pancreas was metastasis, primary leiomyosarcoma of the pancreas had to be ruled out. Histologically, leiomyosarcoma of the pancreas contains interlacing spindle cells with varying degrees of atypia and pleomorphism. The surgical approach to the pancreatic metastases must be aimed complete excision of the tumor with a wide negative margin of clear tissue and maximum preservation of pancreatic remnant if possible. CONCLUSION: In the absence of widespread metastatic disease, aggressive surgical approach with negative margins must be aimed.